Peripheral nerve neurosurgery - Wilson, Thomas ([New York] : Oxford University Press, 2018)
This book presents cases in peripheral nerve surgery divided into four distinct areas of pathology: entrapment and inflammatory neuropathies, peripheral nerve pain syndromes, peripheral nerve tumors, and peripheral nerve trauma. Each chapter also presents pearls for the accurate diagnosis of, successful treatment of, and effective complication management for each clinical entity.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 19, 2018).
Keywords: Nerves, Peripheral -- Surgery; Nervous system -- Surgery